(12-6x)=5(x+4)(6)

Simple and best practice solution for (12-6x)=5(x+4)(6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12-6x)=5(x+4)(6) equation:


Simplifying
(12 + -6x) = 5(x + 4)(6)

Remove parenthesis around (12 + -6x)
12 + -6x = 5(x + 4)(6)

Reorder the terms:
12 + -6x = 5(4 + x)(6)

Reorder the terms for easier multiplication:
12 + -6x = 5 * 6(4 + x)

Multiply 5 * 6
12 + -6x = 30(4 + x)
12 + -6x = (4 * 30 + x * 30)
12 + -6x = (120 + 30x)

Solving
12 + -6x = 120 + 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
12 + -6x + -30x = 120 + 30x + -30x

Combine like terms: -6x + -30x = -36x
12 + -36x = 120 + 30x + -30x

Combine like terms: 30x + -30x = 0
12 + -36x = 120 + 0
12 + -36x = 120

Add '-12' to each side of the equation.
12 + -12 + -36x = 120 + -12

Combine like terms: 12 + -12 = 0
0 + -36x = 120 + -12
-36x = 120 + -12

Combine like terms: 120 + -12 = 108
-36x = 108

Divide each side by '-36'.
x = -3

Simplifying
x = -3

See similar equations:

| x^2-6x-65=0 | | W(2+w)=48 | | f(x)=55x^2-122x-10 | | 33=3a | | Y-7=2(x-0) | | 1.5x+1=11 | | -12+20h+4h-2h=-10 | | 4(x+5)+5=21-x | | -2x-3y=15x+12 | | 2x-(3-3x)=12 | | (5x+10)(4x-10)= | | x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= |

Equations solver categories